COHERENCE ANALYSIS OF THE 2015 INTERNATIONAL CONFERENCE ARTICLE ABSTRACTS IN APPLIED LINGUISTIC - Reski Oktaviani Yuned (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
Coherence is one of the characteristic of good abstract that represent the whole content of research article in order to be able to show what messages want to be expressed. This study investigated the English abstract International conference in applied linguistisc written by Indonesian speaker in its coherence by analyzing the theme and rheme. This study focuses on (1) identifying thematic progressions which are dominantly used in 2015 International conference article abstracts written by non-native speaker of English (2) finding out coherences’ quality of the research article abstract section in 2105 International Conference article abstracts in applied linguistic based on thematic progression. This study was designed by using descriptive qualitative with content anlysis approach. The results show that Zig Zag (Simple Linear) pattern in thematic progression is dominantly used in International Conference Article Abstract then followed by reitaration (Constant) theme, and the last Multiple (Split) pattern. None of the abstracts use Derived TP pattern. Most of the research article abstracts section in International Conference abstracts in applied linguistic have fair quality, just a few included to less quality, none of them was catagorized as good and poor quality. It can be concluded that 2015 International conference article abstracts in applied linguistisc written by Indonesian speakers can be catagorized as good abstract based on their coherence.